Research on Importance Evaluation Method of Semi-rigid Space Frame Structure Members Based on Structural Strain Energy - Guo, Wenlong (International Journal of Natural Resources and Environmental Studies, 2026)
Traditional design of space grid structures typically relies on the assumption of pinned joints. While this simplification streamlines the evaluation of member importance, it fails to account for the semi-rigid behavior of actual connections. This discrepancy often leads to inaccuracies in structural analysis and member importance ranking, introducing potential risks of misjudgment. To overcome these limitations, this study develops a more refined evaluation framework. First, a high-fidelity finite element model (FEM) of a semi-rigid space grid was established, incorporating joint rotational stiffness. Members were simulated using segmented beam elements, and the model's accuracy was rigorously validated against experimental data. Subsequently, a comprehensive evaluation index was proposed based on structural strain energy, which integrates multiple internal force components, including axial force, bending moment, and shear force. Finally, the proposed method was applied to a regular square pyramid space grid to compare member importance rankings against traditional methods. The underlying internal force redistribution mechanisms were analyzed by selecting representative members with significant ranking discrepancies. The results indicate that while both methods show consistent trends for most members, substantial differences exist in critical regions, such as the top chords. Mechanism analysis reveals that the traditional pinned-joint model, by neglecting moment transfer, results in simplified load paths and stress concentrations, thereby overestimating the importance of specific members. In contrast, the semi-rigid model accurately reflects the diversified load-transfer mechanisms facilitated by joint moments. This study confirms that joint semi-rigidity significantly influences the assessment of member importance. The proposed method effectively identifies and corrects misjudgments caused by the pinned-joint assumption, providing a more reliable theoretical basis for identifying critical components and optimizing maintenance strategies, particularly for complex space structures requiring high assessment precision.